Synthesis of precipitated Calcium Carbonate (PCC) From Lime Rock Nature Methods Caustic Soda (Studies Concentration HNO3) - Noor Isnaini Azkiya; Fanny Prasetia; Elsa Desyta Putri; Anggita Rosiana; Sri Wardhani (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2016)
The limestones was abundant in Tuban, East Java and have high calcium mineral content. Nevertheless, in the economic value, limestone have low price. Aim the research is prepare Precipitated Calcium Carbonate (PCC) by caustic soda method. In this method, calcium was dissolved in HNO3 with different concentration (2, 4,6, 8 M). The Filtrate obtained then was added by Na2CO3 1 M to get PCC. As the results, The white PCC obtained with the highest rendement is 64,7% when added HNO3 6M. Analysis of functional group by FTIR show that there were strong absorption in the 844,76; 912,27 dan 1411,40 cm-1 that indicated carbonate group. Analysis of Cristallinity by XRD show that there were the peak characteristic of 2 on 29,50˚; 36,07˚ dan 39,50˚that representative calcite structure. SEM-EDX Analysis show that PCC have a mixing structure of calcite and vaterite. Keywords: limestone, PCC, caustic soda